Deni Plant Names - Kaufman, Terrence (Revista Brasileira de Linguística Antropológica, 2021)
This article is a report on Deni ethnobotanical terms and their indigenous speakers’ classification/taxonomy collected from two speakers in 1993 at Porto Velho, nly Rondônia. The transcriptions are believed to be phonologically accurate, but the work reported on is the only work I have done on Deni, so occasional errors may be present.